Technology surveillance of the solar refrigeration by absorption/adsorption - Merino, Jose Carlos Alvarez (2016)
PICMET 2016 - Portland International Conference on Management of Engineering and Technology: Technology Management For Social Innovation, Proceedings4 January 2017, Article number 7806767, Pages 1976-19822016 Portland International Conference on Management of Engineering and Technology, PICMET 2016; Honolulu; United States; 4 September 2016 through 8 September 2016; Category numberCFP16766-ART; Code 125891